2007
DOI: 10.1016/j.bbr.2006.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine does not produce state-dependent effects on learning in a Pavlovian appetitive goal tracking task with rats

Abstract: Past research has shown that when rats received 0.4 mg base/kg nicotine paired reliably with intermittent sucrose delivery that anticipatory sucrose-seeking behavior (i.e., goal tracking) was differentially displayed in the nicotine state relative to intermixed saline sessions in which no sucrose was delivered. The present research extended this observation to a lower dose of nicotine (i.e., 0.2 mg base/kg) and tested a state-dependent learning account of differential conditioned responding. According to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
2
20
2
Order By: Relevance
“…Albeit possible, we have published data that suggests that this possibility is unlikely (Bevins et al, 2007;. In these studies, the nicotine stimulus, along with all the chamber stimuli, was paired with sucrose on every session.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Albeit possible, we have published data that suggests that this possibility is unlikely (Bevins et al, 2007;. In these studies, the nicotine stimulus, along with all the chamber stimuli, was paired with sucrose on every session.…”
Section: Discussionmentioning
confidence: 98%
“…To test this possibility, rats were treated with saline rather than nicotine for the first time. Removal of the nicotine stimulus did not significantly disrupt goal-tracking behavior (Bevins et al, 2007;, suggesting that nicotine in these studies was not a sufficiently salient stimulus element to acquire control of behavior when the external chamber cues were as good of a predictor. In the present study, these chamber cues were even a better predictor than nicotine.…”
Section: Discussionmentioning
confidence: 98%
“…To the contrary, not all states and contexts produce memory dependency effects. For instance, people do not exhibit memory dependency effects for chewing gum (e.g., Miles & Johnson, 2007;Overman, Sun, Golding, & Prevost, 2009), nicotine (e.g., Bevins, Penrod, & Reichel, 2007), or stress (e.g., Thompson et al, 2001). Therefore, given that memory-dependency effects can occur for self-aspects (as we have shown here), it raises the question of what these various internal states, external contexts, and self-aspects have in common that enables them to elicit memory dependency effects.…”
Section: Discussionmentioning
confidence: 99%
“…Goal-tracking refers to approach behavior to a location where the reinforcer has occurred in the past (Boakes, 1977; Farwell and Ayres, 1979). Previous research has shown that this acquired appetitive behavior controlled by the nicotine stimulus does not reflect state-dependent learning (Bevins et al, 2007; Murray and Bevins, 2011), cannot be attributed to a non-associative or stimulant effect of nicotine (Besheer et al, 2004; Murray et al, 2009; Reichel et al, 2007; Wilkinson et al, 2006), and follows many postulates of Pavlovian conditioning (Bevins and Murray, 2011; Murray et al, 2009). …”
Section: Introductionmentioning
confidence: 89%